Recent progress in pendant rhodamine-based polymeric sensors for the detection of copper, mercury and iron ions. Issue 12 (2nd December 2021) - Choudhury, Neha; De, Priyadarsi
Abstract: Monitoring of trace amount of toxic metal ions in aqueous and biological systems is vital because exposure to even low concentrations of toxic metal ions can have severe consequences on human health and the environment. Various synthetic methodologies are utilized to fabricate chemosensors that can specifically detect these toxic metal ions with high sensitivity. Recently, fluorescent sensors, particularly the rhodamine derivatives, have been considered as one of the most promising candidates for the recognition of metal ions owing to their attractive highlights. In this context, polymeric sensors bearing pendant rhodamine units have significant benefits over rhodamine-based small molecular sensors because of high-aqueous solubility, improved stability, signal amplification, easy fabrication into devices, etc. Eventually, the aforementioned factors have persuaded scientists to grow such novel polymeric sensors. This review aims to summarize the recent advancements (2011–present) toward pendant rhodamine-based polymeric sensors for the detection of copper (Cu 2+ ), mercury (Hg 2+ ) and iron (Fe 3+ ) ions. The sensing mechanism of these polymeric sensors typically depends on the structural switch between non-fluorescent spirocyclic derivative and highly emissive ring-opened amide isomer. Consequently, we anticipate that this work can provide an extensive outline of key angles related to the planning of rhodamine-affixed polymeric sensors for the detection of toxic metal ions. Graphical Abstract: UF0001